Effect of informed consent on patient characteristics in a stroke thrombolysis trial. (26th September 2017) - Thomalla, Götz; Boutitie, Florent; Fiebach, Jochen B.; Simonsen, Claus Z.; Nighoghossian, Norbert; Pedraza, Salvador; Lemmens, Robin; Roy, Pascal; Muir, Keith W.; Heesen, Christoph; Ebinger, Martin; Ford, Ian; et al.
Abstract : Objective: To determine whether the manner of consent, i.e., informed consent by patients themselves or informed consent by proxy, affects clinical characteristics of samples of acute stroke patients enrolled in clinical trials. Methods: We analyzed the manner of obtaining informed consent in the first 1, 005 patients from WAKE-UP, an investigator-initiated, randomized, placebo-controlled trial of MRI-based thrombolysis in stroke patients with unknown time of symptom onset running in 6 European countries. Patients providing informed consent by themselves were compared with patients enrolled by proxy consent. Baseline clinical measures were compared between groups. Results: In 359 (35.7%) patients, informed consent was by proxy. Patients with proxy consent were older (median 71 vs 66 years, p < 0.0001) and had a higher frequency of arterial hypertension (58.2% vs 43.4%, p < 0.0001). They showed higher scores on the NIH Stroke Scale (median 11 vs 5, p < 0.0001) and more frequently aphasia (73.7% vs 20.0%, p < 0.0001). The rate of proxy consent varied among countries ( p < 0.0001), ranging from 77.1% in Spain to 1.2% in Denmark. Conclusions: Patients recruited by proxy consent were older, had more severe strokes, and had higher prevalence of aphasia than those with capacity to give personal consent. Variations in the manner of consent across countries may influence trial results. Clinicaltrials.gov and Clinicaltrialsregister.eu identifiers: NCT01525290 (clinicaltrials.gov ); 2011-005906-32 (clinicaltrialsregister.eu).